Modifications of Cell Signalling and Redox Balance by Targeting Protein Acetylation Using Natural and Engineered Molecules: Implications in Cancer Therapy - Venkateswaran, Kavya; Verma, Amit; N. Bhatt, Anant; K. Agrawala, Paban; G. Raj, Hanumantharao; Malhotra, Shashwat; K. Prasad, Ashok; De Wever, Olivier; E. Bracke, Marc; Saso, Luciano; S. Parmar, Virinder; Shrivastava, Anju; et al. (Current Topics in Medicinal Chemistry, 2014)
Acetylation of proteins with the addition of an acetyl group on the lysine residue is one of the vital posttranslational modifications that regulate protein stability, function and intracellular compartmentalization. Like other posttranslational modifications, protein acetylation influences many if not all vital functions of the cell. Protein acetylation has been originally associated with histone acetylation regulated by Histone Acetyl Transferase (HAT) and Histone Deacetylase (HDAC) and was mainly considered to be involved in epigenetic regulation through chromatin remodelling. It is now widely referred to as lysine acetylation orchestrated by lysine acetyl transferase (KAT) and lysine deacetylase (KDAC) and influences many cellular functions. Protein acetylation fine tunes the redox balance and cell signalling in the context of cancer by exerting its control on expression of two very important redox sensors viz. Nrf2 and NF-ΚB. Accumulating evidences show that inhibitors of deacetylase (KDACi), responsible for cytotoxic effects in cancer cells, mediate their actions by inhibiting the deacetylases, thereby simulating an hyperacetylation state of histone as well as non-histone proteins, similar to the one created by KATs. Emergence of calreticulin (CRT) mediated protein acetylation system using polyphenolic acetates as donors coupled with over expression of CRT has opened new avenues for targeting protein acetylation for improving cancer therapy. Modifiers of protein acetylation are therefore, emerging as a class of anticancer therapeutics and adjuvant as they inhibit growth, induce differentiation and death (apoptosis) differentially in cancer cells and also exhibit chemo-radiation sensitizing potential. Although pre-clinical investigations with many natural and synthetic KDAC inhibitors have been very promising, their clinical utility has so far been limited to certain types of cancers of the hematopoietic system. The future of protein acetylation modifiers appears to depend on the development of newer engineered molecules and their rational combinations that can exploit the differences in the regulation of protein acetylation between tumor and normal cells/tissues.
Keywords: HDACi